DALIH KEADILAN DAN ERROR JURIS SEBAGAI ALASAN MELEPASKAN TERDAKWA DARI SEGALA TUNTUTAN HUKUM - Shidarta Shidarta (Komisi Yudisial RI, 2011)
ABSTRACTThere are many conditions that could be determined as valid defences in court decisions. Some have been specified in the Indonesian Criminal Code but others appear from legal practices. In the verdict number 583/Pid.B/2010/PN Jkt Sel., panel of judges concluded that the accused was unpunishable due to the existence of valid defences related to legal justice, moral justice, and social justice. This article scrutinizes those reasons of the valid defence and comes to the conclusion that judges failed to support their arguments. The author refers to